Ten new species of Triclistus Förster, 1869 (Hymenoptera, Ichneumonidae) from Peru, with a key to Neotropical species - Alvarado, Mabel; Rodriguez-Berrio, Alexander (Zootaxa, 2013)
Triclistus Förster, 1869 is a widely distributed genus of the family Ichneumonidae, rich in the Old World but poorly represented in the Neotropical region. Ten new species are described: Triclistus ashaninka sp. n., Triclistus bicolor sp. n., Triclistus castilloai sp. n., Triclistus cholo sp. n., Triclistus muqui sp. n., Triclistus inti sp. n., Triclistus matsiguenga, sp. n., Triclistus megantoniensis sp. n., Triclistus warmi sp. n. and Triclistus yungas sp. n. A key to Neotropical species is also presented, and four species group are suggested, based in the head and propodeum structure.